Producing/reproducing ideology: unearthing multiple perspectives on literature and popular culture - Shahizah Ismail Hamdan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Literature and Popular Culture, a course in the MA Postcolonial Literature in English exposes students to the manifestations of popular culture in literature. By examining various popular literary genres, the students are trained to see the significance of popular culture within everyday realities using rhetorical methods as well as critical theories. As part of their research paper, students are required to observe, reflect, describe and critically analyse several forms of popular culture and expected to understand how some literary works evolve from high culture to popular culture, thus becoming a significant force in the everyday lives of the masses. However, as the course involves a study of the types of popular culture mostly originating from the West, students find it difficult to identify the underlying patterns prevalent in the texts. In addition, although the students come from diverse non-Western ethnic backgrounds, their interpretations are one-dimensional, usually projecting the mainstream views. As ideology is a prevalent concept in popular culture, it is felt that an understanding of this concept will help them to develop multiple perspectives in their study of literature and popular culture. Therefore, this paper will focus on how understanding ideology can be an intervention method into unearthing multiple meanings in literature and popular culture.